Model Keperawatan Keluarga Santun Lansia dalam Upaya Peningkatan Kualitas Asuhan Keluarga pada Lansia: A Literature Review - Etty Rekawati; Achir Yani S. Hamid; Junaiti Sahar; Widyatuti Widyatuti; Ni Luh Putu Dian Yunita Sari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Family is the closest person to the elder person who has an important role in caring for elder person. The purpose of this study is to provide an overview of the cordial older family nursing model in an effort to improve the quality of family care in elder person. The study approach was the study of literature with expert agreement. The search method for library resources was done online, which uses databases such as Science Direct, Scopus, Sage, Pubmed and ProQuest. The keywords used were "elder mistreatemnt", "intervention" and "family approach". Literature search was only limited in 2008 to 2019 and in English. The results obtained 15 research articles analyzed. There were three themes obtained, namely the provision of information through training, giving positive perceptions to families who care for the elderly and counseling. Training was oriented towards family coping and coping strategies in caring for the elder person aimed at caregivers, cadres and health workers. Planting suggestions were given in groups or individually to families who care for the elderly, and counseling is given individually to families who need it. Further research is expected to be able to identify the quality of life of the elder person related to the application of the cordial older family nursing model. Keywords: elderly; the cordial older family nursing model; family care quality ABSTRAK Keluarga merupakan orang terdekat lansia yang memilki peran penting dalam merawat lansia. Tujuan dari penulisan ini adalah memberikan gambaran model keperawatan keluarga santun lansia dalam upaya peningkatan kulitas asuhan keluarga pada lansia. Pendekatan studi adalah studi literatur dengan kesepakatan pakar. Metode pencarian sumber pustaka dilakukan online yaitu menggunakan basis data seperti Science Direct, Scopus, Sage, Pubmed dan ProQuest. Kata kunci yang digunakan adalah “elder mistreatment”, “intervention” dan “family approach”. Penelusuran literatur hanya dibatasi dalam tahun 2008 hingga 2019 dan dalam bahasa Inggris. Hasil yang didapatkan adalah didapatkan 15 artikel penelitian yang dianalisis. Ada tiga tema yang didapatkan, yaitu pemberian informasi melalui pelatihan, pemberian persepsi positif pada keluarga yang merawat lansia dan konseling. Pelatihan berorientasi pada dukungan dan strategi koping keluarga dalam merawat lansia yang ditujukan kepada pelaku rawat, kader dan petugas kesehatan. Penanaman sugesti diberikan secara berkelompok ataupun individual pada keluarga yang merawat lansia, dan konseling diberikan secara individual bagi keluarga yang memerlukannya. penelitian lanjutan diharapkan dapat mengidentifikasi mengenai kualitas hidup lansia yang berkaitan dengan penerapan model keperawatan santun lansia. Kata kunci: lansia; model keperawatan keluarga; kualitas asuhan keluarga